Peran mediasi komitmen afektif pada persepsi dukungan organisasi terhadap kinerja karyawan - Chaidir, John; Haerofiatna, Haerofiatna; Kania, Dewi; Wahyudi, Wahyudi (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2023)
Organizations are often faced with problems with their employees, employee performance is one of them. Employees are the key to the success of an organization. The purpose of this study is to investigate the extent to which the mediating role of affective commitment on perceived organizational support will ultimately have an impact on improving employee performance. This study uses a quantitative method with a PLS-SEM approach, and data collection using a questionnaire. The results of this study, all proposed hypotheses are entirely accepted, where the perception of organizational support has an effect on increasing employee performance and affective commitment, then affective commitment has a significant impact on increasing employee performance. On the other hand, affective commitment can have a partial mediating effect on the perceived organizational support on employee performance.